Interactions between noradrenaline and corticosteroids in the brain: from electrical activity to cognitive performance - Krugers, Harmen J.; Karst, Henk; Joels, Marian (Frontiers in Cellular Neuroscience, 2012)
One of the core reactions in response to a stressful situation is the activation of the hypothalamus–pituitary–adrenal (HPA) axis which increases the release of glucocorticoid hormones from the adrenal glands. In concert with other neuro-modulators, such as (nor)adrenaline, these hormones enable and promote cognitive adaptation to stressful events. Recent studies have demonstrated that glucocorticoid hormones and noradrenaline, via their receptors, can both rapidly and persistently regulate the function of excitatory synapses which are critical for storage of information. Here we will review how glucocorticoids and noradrenaline alone and in synergy dynamically tune these synapses in the hippocampus and amygdala, and discuss how these hormones interact to promote behavioral adaptation to stressful situations.